Etika Bisnis Islam dalam E-Commerce di Era VUCA - Rika Nur Amelia; Silvi Indah Nurvita Sari; Anugrahi Putri Ziyadatin Ilmi; Hikmatus Sa’diyah; Ananta Delyana Mafikah; Eny Latifah (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
The VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era has changed the way businesses operate, including in the realm of E-Commerce. These changes raise new challenges, such as intense competition, market uncertainty, and the need for rapid adaptation. In this context, Islamic business ethics offers relevant and adaptive guidance through values ​​such as honesty (ṣidq), justice (ʿadl), responsibility (amānah), and transparency (shafāfiyyah). This research aims to analyze the application of the Islamic business ethics perspective in E-Commerce operations in the VUCA era. This article uses a qualitative approach, with a library research method to integrate Islamic ethical principles. The research results show that the application of Islamic business ethics can strengthen consumer trust, increase operational stability, and create a sustainable business model amidst uncertainty. This article concludes that the integration of Islamic business ethical values ​​is not only relevant but also provides innovative solutions to answer the challenges of the VUCA era.